GENETIC SOLUTION METHODS FOR PROBLEM OF STORES SHIPMENT OPTIMAL PLANNING - Alina V. Basova; Pavel G. Belyavskiy (Advanced Engineering Research)
A genetic algorithm for solving the optimization problem of stores shipment is developed. The algorithm permits to find a good approximate solution, and it has acceptable computational complexity.